Effect of low temperature storage on quality and total phenolics of Thai eggplant (Solanum melongena cv. Gelatik) - Utami, D. R. (2020)
In Indonesia, Thai eggplant is one of indigenous vegetables mostly in West Java, which is consumed in “baby” stages and fresh condition as ready-to-serve vegetable. Thai eggplant is rich of phenolics as antioxidant. Low temperature storage is commonly method in extending shelf life of vegetables. However, there is no study related on the effect on low temperature storage on the quality changes in Thai eggplant. The aim of this study was to analyze the effect of low temperature storage on quality and total phenolics of Thai eggplant. Sample of vegetables in the same shape and ripening stage were harvested, sorted, washed, dried and selected sample stored in low temperature storage at 5±1, 10±1, 15±1°C and RH 90-95% for 18 days. The results show that highest weight loss and changes in firmness occured at 15°C, whereas value of yellowness to blueness (b value) in all treatment increased. Highest lightness reduction on flesh happened at 5°C (15.58%), and highest chilling injury of flesh and seed at 5°C. Flesh browning at 4th day for those sample of vegetables stored at 5 and 10°C. Highest and the most rapid chilling injury index increasing at 5°C, Thai eggplant was more sensitive to chilling injury symptoms. Total phenolics decreased significantly during 18 days storage, and vegetables were stored at 10°C could maintain total phenolics better than other low temperatures. Thai eggplant was suggested to store at 10°C as the best low temperature.